Reproductive potential and growth of Stolephorus bataviensis from Dakshina Kannada coast - Doddamani, M; Ramesha, T J; Laxmipathi, M T; Annappaswamy, T S; Shanbhogue, S L (Indian Journal of Fisheries, 2011)
The reproductive potential and growth aspects of Stolephorus bataviensis have been studied. The fish showed intermittent spawning throughout the year with peak activity during March-May. Males appear to mature earlier than females. The fecundity ranged from 898 to 2436 eggs per individual. Life span of S. bataviensis was found to be 1.53 years and the Von Bertallanffy growth equation was Lt=11.77 (l-e-0.1629(t+0.0540)).